2014
DOI: 10.1111/pcn.12209
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared spectroscopy for examination of prefrontal activation during cognitive tasks in patients with major depressive disorder: A meta‐analysis of observational studies

Abstract: Aims: Near-infrared spectroscopy has the potential for aiding the diagnosis of major depressive disorder. The purpose of this study was to systematically review the evidence from observational studies regarding the use of near-infrared spectroscopy in patients with major depressive disorder and to identify the characteristic pattern of prefrontal lobe activity in major depressive disorder.Methods: MEDLINE, PubMed, Cochrane Library and Web of Science databases were searched in December 2013. All case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 45 publications
8
39
0
Order By: Relevance
“…NIRS is a non-invasive method to assess CBF by measuring hemoglobin concentration using nearinfrared light absorption in the brain, and has been widely applied to mental disorders, including depression. 13 Although spatial resolution is less precise in NIRS in comparison with other techniques, including functional magnetic resonance imaging and single-photon emission computed tomography, NIRS has the advantage in the temporal resolution and was adequate for simultaneous measurement with magnetic stimulation in the present study. The results support the usefulness of fHbC measurement during TMS for evaluating its clinical effectiveness.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…NIRS is a non-invasive method to assess CBF by measuring hemoglobin concentration using nearinfrared light absorption in the brain, and has been widely applied to mental disorders, including depression. 13 Although spatial resolution is less precise in NIRS in comparison with other techniques, including functional magnetic resonance imaging and single-photon emission computed tomography, NIRS has the advantage in the temporal resolution and was adequate for simultaneous measurement with magnetic stimulation in the present study. The results support the usefulness of fHbC measurement during TMS for evaluating its clinical effectiveness.…”
mentioning
confidence: 71%
“…We used near‐infrared spectroscopy (NIRS) to measure frontal cerebral hemoglobin concentration (fHbC) reflecting cerebral blood volume during stimulation and assessed the relation with treatment effectiveness. NIRS is a non‐invasive method to assess CBF by measuring hemoglobin concentration using near‐infrared light absorption in the brain, and has been widely applied to mental disorders, including depression . Although spatial resolution is less precise in NIRS in comparison with other techniques, including functional magnetic resonance imaging and single‐photon emission computed tomography, NIRS has the advantage in the temporal resolution and was adequate for simultaneous measurement with magnetic stimulation in the present study.…”
mentioning
confidence: 85%
“…So far, numerous studies, using multi-channel NIRS, have provided evidence that NIRS signals could work as promising diagnostic biomarkers for MDD, bipolar disorder, and schizophrenia. In fact, oxy-Hb activation during a verbal fluency task (VFT) (a straight-forward task for assessment of executive function) has consistently been reported to be decreased in MDD patients, compared with healthy controls (Matsuo et al, 2002, Matsuo et al, 2005, Suto et al, 2004, Takizawa et al, 2014, Tomioka et al, 2015, Usami et al, 2014, Zhang et al, 2015). In addition, a recent multi-site study found that frontal hemodynamic patterns detected with NIRS during a short VFT differentiated MDD patients from those with bipolar disorder or schizophrenia with > 70% accuracy (Takizawa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This would have had 80% power to detect an ES of 0.5 with a two-sided alpha level of 0.05 between groups and an ES of 0.57 with a two-sided alpha level of 0.05 between groups. A meta-analysis of fNIRS studies in depressed patients 145 found an ES difference compared with control subjects of 0.74 in frontal cortex HbO response to cognitive tasks activating the frontal cortex.…”
Section: Sample Sizementioning
confidence: 99%